BRITAIN: REWARDING BULLIES. - BHADANI, ANITA (New Internationalist)
The article discusses the recent US-UK trade deal, which is characterized as more of a press release than a substantive agreement, lacking legal binding and containing minimal commitments. British Prime Minister Keir Starmer's concessions are seen as a response to pressure from the US, particularly from President Trump, with future negotiations potentially threatening rights and standards in Britain. The article raises concerns about the implications of trade provisions on everyday life, including healthcare and digital rights, and highlights the risk of adopting a more deregulatory approach in the UK, particularly regarding technology and data access.